THE STATE OF TRANSFORMATIVE CON-SUMER RESEARCH MOVEMENT : Systematic literature review on research streams and methods - Haapanen, Ida (My University, 2020)
Transformative consumer research (hereafter TCR) is an area of consumer research that emerged in the 21st century and, by its definition, seeks to improve well-being through socially impactful research. This line of research is known for not only seeking to increase consumption or increase sales efficiency but rather to gain an understanding of how the consumer decision-making process is formed and influenced. Thus, it seeks to find significant results in reducing, for example, the consumption of goods and services that are detrimental to health, such as intoxicants, gambling, and unhealthy food. The TCR movement has set itself high objectives with six core qualities. These core qualities include improvement of well-being, diversity of perspectives, use of precise methods and theories, emphasis on socio-cultural and situational contexts, co-operation with consumers, and dissemination of results to relevant stakeholders. This systematic literature review focused on the TCR movement as a research phenomenon. It examined what topics have been studied under the TCR movement, and by what methods. In addition, the screened TCR articles were mirrored to the core qualities mentioned above to examine whether the TCR movement meets the criteria it has set for itself. The review created an overall picture of what the current state of the TCR movement is. The review was limited to TCR articles that define themselves under the TCR movement by using the name of the research direction in either the research title, keywords, or abstract. As a result, it became clear that reviewed TCR articles explored a variety of themes. Thematically, the articles were divided into articles exploring consumption phenomena as well as articles exploring the TCR movement itself. The improvement of well-being was emphasized in all the studies focusing on consumption, and there was a relatively large number of studies focusing on food and physical or mental health in particular. Other popular topics were consumer empowerment and economic maintenance phenomena. Versatility was also emphasized in the research methods used. In terms of methods, the most significant finding was the small proportion of longitudinal research.

Transformatiivinen kuluttajatutkimus (lyhennettynä TCR) on 2000-luvulla syntynyt kuluttajatutkimuksen osa-alue, joka oman määritelmänsä mukaan pyrkii parantamaan hyvinvointia sosiaalisesti vaikuttavien tutkimusten kautta. Tutkimussuunta on tunnettu siitä, että se ei pyri vain lisäämään kulutusta tai tehostamaan myyntiä, vaan tavoittelee pikemminkin ymmärrystä siitä, miten kuluttajien ostoprosessiin voi vaikuttaa. Täten se pyrkii löytämään merkittäviä tuloksia esimerkiksi terveyteen haitallisesti vaikuttavien hyödykkeiden ja palvelujen, kuten päihteiden, rahapelien ja epäterveellisen ruoan kuluttamisen vähentämisestä. TCR-liike on asettanut itselleen kovat tavoitteet kuuden ydinominaisuuden myötä. Näitä TCR:lle leimallisia ominaisuuksia ovat hyvinvoinnin parantaminen, näkökulmien monipuolisuus, tarkat metodit ja teoriat, sosiokulttuuristen ja olosuhteellisten kontekstien korostaminen, kuluttajien kanssa tehtävä yhteistyö sekä relevanteille sidosryhmille levitettävät tulokset. Tämä systemaattinen kirjallisuuskatsaus keskittyi tutkimaan TCR tutkimusilmiönä – aihealueita, joihin tutkimus keskittyy sekä metodeja, joita tutkimuksissa on käytetty. Lisäksi valittuja TCR-artikkeleita tarkasteltiin sen mukaan, täyttävätkö ne yllämainitut, TCR liikkeen itselleen asettamat kriteerit. Tarkastelulla luotiin kokonaiskuvaa siitä, mikä on TCR-liikkeen nykytila. Tarkastelu rajattiin TCR-artikkeleihin, jotka itse määrittävät itsensä kuuluvaksi TCR-liikkeen alle käyttämällä tutkimussuunnan nimeä joko tutkimuksen nimessä, avainsanoissa tai tiivistelmässä. Tuloksena selvisi, että TCR-artikkelit tutkivat monipuolisesti erilaisia teemoja. Temaattisesti artikkelit jakaantuivat kuluttamisen ilmiöitä tutkiviin artikkeleihin sekä artikkeleihin, jotka tutkivat TCR-liikettä itsessään. Hyvinvoinnin parantaminen korostui kaikissa kuluttamiseen keskittyvissä tutkimuksissa ja etenkin ruokaan sekä fyysiseen tai henkiseen hyvinvointiin keskittyvät aiheet toistuivat monissa artikkeleissa. Muita suosittuja aihealueita olivat kuluttajien voimaannuttaminen ja talouden ylläpitoon liittyvät ilmiöt. Tutkimustavoissa korostui niin ikään monipuolisuus. Metodien suhteen merkittävimmäksi löydökseksi osoittautui lognitudiaalisen tutkimuksen pieni osuus.
Keywords: Transformative consumer research, systematic literature review, content analysis